Comprehensive Physiology 2010
DOI: 10.1002/cphy.c090003
|View full text |Cite
|
Sign up to set email alerts
|

Gaseous Therapeutics in Acute Lung Injury

Abstract: Acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) remain major causes of morbidity and mortality in critical care medicine despite advances in therapeutic modalities. ALI can be associated with sepsis, trauma, pharmaceutical or xenobiotic exposures, high oxygen therapy (hyperoxia), and mechanical ventilation. Of the small gas molecules (NO, CO, H₂S) that arise in human beings from endogenous enzymatic activities, the physiological significance of NO is well established, whereas that of CO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 202 publications
0
14
0
Order By: Relevance
“…Gas molecules have been proposed as therapeutic agents for a variety of disease processes, including lung and even systemic illnesses (36, 37). One such gas is CO, which has been shown to be beneficial therapeutically in animal models of sepsis (16, 20, 21).…”
Section: Discussionmentioning
confidence: 99%
“…Gas molecules have been proposed as therapeutic agents for a variety of disease processes, including lung and even systemic illnesses (36, 37). One such gas is CO, which has been shown to be beneficial therapeutically in animal models of sepsis (16, 20, 21).…”
Section: Discussionmentioning
confidence: 99%
“…They observed that the plasma and leukocyte lipid mediator profiles in baboons with pneumonia were significantly shifted, with a reduction in the pro-resolution phenotype. However, this could be partially reversed by inhalation of CO. CO has shown therapeutic potential in animal models of acute lung injury, including those involving endotoxin challenge, oxidative lung injury, ischemia-reperfusion injury, pulmonary fibrosis, ventilator-induced lung injury, and lung transplantation [98,107]. Inhaled CO is presently being assessed in clinical trials to determine if it can improve lung function and survival in a critical care setting.…”
Section: Carbon Monoxidementioning
confidence: 99%
“…and has a protective function in inflammatory diseases (24). With a systems approach, we recently reported that low-dose inhaled CO accelerates resolution of acute inflammation in mice, enhances human and mouse macrophage phagocytosis and efferocytosis, and temporally regulates local lipid mediators (LM) (7).…”
mentioning
confidence: 99%